2021
DOI: 10.46754/umtjur.2021.04.003
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF ENRICHED COPEPODS ON THE GROWTH, SURVIVAL AND COLOURATION OF ANGELFISH (Pterophyllum scalare)

Abstract: Cyclopoid copepod has a potential as live feed that can provide ornamental fish larvae with energy and essential nutrients, and promote their growth and survival, as well as affect their colouration. However, the nutrition, growth and nutritional requirements of this species are poorly understood. This research focuses on comparing the efficacy of enrichment types on copepods towards the growth rate, survival rate and colouration of Pterophyllum scalare larvae. The enrichment of copepods consists of four enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Copepods are a good food source for fish larvae because they have a better biochemical profile than traditional live feeds such as rotifers and Artemia [ 3 , 4 ]. Researchers have shown that copepods increase fish larvae survival, growth, health, pigmentation, and tolerance to the stressors of rearing conditions [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Copepods are a good food source for fish larvae because they have a better biochemical profile than traditional live feeds such as rotifers and Artemia [ 3 , 4 ]. Researchers have shown that copepods increase fish larvae survival, growth, health, pigmentation, and tolerance to the stressors of rearing conditions [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%